Counterfeiting of Skincare Products Under Law Number 8 of 1999 on Consumer Protection Article 62 Paragraph (1) From the Perspective of Islamic Criminal Law - Sita Jahrotun Nisa; Enceng Arif Faizal; Muhammad Fauzan Januri (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Counterfeiting of skincare products is a form of criminal offense that not only causes economic losses to consumers but also poses serious risks to public health due to the use of hazardous substances that fail to meet established safety standards. This issue has become increasingly alarming with the growing circulation of illegal skincare products through various trading channels, both offline and online. This study aims to analyze the elements of the criminal offense of skincare product counterfeiting as regulated under Article 62 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection and to examine the issue from the perspective of Islamic Criminal Law, particularly regarding criminal liability and the sanctions that may be imposed on offenders. This research employs a normative juridical method using statutory and conceptual approaches supported by library research. The findings indicate that the counterfeiting of skincare products fulfills the elements of criminal liability under Indonesian positive law and, within the framework of fiqh jinayah, may be classified as a jarimah ta'zir. The novelty of this study lies in its integration of the analysis of Article 62 paragraph (1) of the Consumer Protection Law with the concept of ta'zir punishment as an effort to strengthen consumer protection. Therefore, the imposition of criminal sanctions serves as an important instrument for protecting society and preventing the circulation of harmful skincare products.